Managing Artificial Intelligence-Driven Platforms for Student Development - Abdullahi, Nimota Jibola Kadir (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2025)
This study examines the impact of AI-driven platforms, including personalized learning platforms, smart content, and intelligent tutoring systems, on students’ cognitive development, problem-solving skills, and overall academic performance. A structured survey was used to gather data for the study. The undergraduate students in the faculties of education of public universities in Kwara State, Nigeria, were the target population. Data were analyzed using SmartPLS tools to evaluate the relationship between AI-driven platforms and student development. The findings indicate that the effective management of artificial intelligence-driven learning platforms, including personalized learning platforms, smart content, and intelligent tutoring systems, has a significant impact on student development (engagement, academic achievement, and cognitive capacities) in higher education institutions. This study shows empirical support for AI’s role in contemporary education and how AI-driven tools may effectively promote personalized learning and adaptive learning experiences. Although AI in education is widely discussed, there has been little empirical research examining how AI directly affects the growth of Nigerian students.